ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRICE EARNING RATIO PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2009-2012 - (B11110046), Gunawan Hidayat (Jurnal Manajemen Update, 2014)
One of the fundamental analysis of the most frequently used by investors and securities analysts in assessing the price of a stock is the approach of Price Earning Ratio (PER). Price Earning Ratio (PER) indicates how much investors are willing to pay for each dollar of profit. This study aims to examine the influence of Dividend Payout Ratio (DPR), Firm Size, Earnings Growth and Return On Equity (ROE) to the Price Earning Ratio (PER). The research sample used as many as 12 companies in the corporate sector, Property and Real Estate. The data used are secondary data from the Property and Real Estate companies listed in Indonesia Stock Exchange for 4 years ie 2009, 2010, 2011 and 2012 Sampling was done by purposive sampling. Data were analyzed using multiple regression analysis tool were preceded by the classical assumption that consist of normality test, multicollinearity, heteroscedasticity test and autocorrelation test. Hypothesis testing is performed using the F test and t test with significance level Î± = 0.05. Simultaneous test results indicate that all the independent variables significantly influence the price earning ratio (PER). Partial test results indicate that the variable Dividend Payout Ratio (DPR) has a negative and significant effect on the price earning ratio (PER), Firm Size has a positive and significant impact on the price earning ratio (PER), Earnings Growth and does not have a significant negative effect on Price Earning Ratio (PER), and Return on Equity (ROE) has a negative and significant impact on the price earning ratio (PER). Keywords : Dividend Payout Ratio, Firm Size, Earnings Growth And Return On Equity, Price Earning Ratio.